The Pagih book: An early detection and intervention instrument nutrition-monitoring for preventing the triple burden malnutrition in the golden age - Della Ayu Vilasanty Putri; Septianda Salsabila Prima; Hilyatus Fathiyah Afni Febriana (Public Health Risk Assesment Journal, 2026)
Background: The triple burden of malnutrition, encompassing undernutrition, micronutrient deficiencies, and overnutrition, remains a major nutritional problem in Indonesia, particularly among pregnant women and young children. Based on the 2023 Indonesian health survey, the prevalence of chronic energy deficiency (CED) among pregnant women reached 16.9%, anemia 27.7%, and exclusive breastfeeding was only 66.4% according to the 2024 Indonesian Nutritional Status Survey (Survei Status Gizi Indonesia, SSGI). These data indicate that the risk of malnutrition, especially among pregnant women from lower-middle socioeconomic backgrounds, remains high and has not been optimally addressed. Methods: This paper uses a literature review and conceptual paper approach, employing a gap analysis method for existing nutrition monitoring media. Data was obtained from scientific journals, national reports, and observations of nutrition worker needs in primary health care. Findings: Findings show that the Pagih Book is designed with three main functional components, namely recording daily nutritional intake through simple food notes and visualization of MyPlate contents, monitoring nutritional status and risk through the wrap-around curve of pregnant women's weight gain and micronutrient deficiency checklist, and integration of education and continuous nutritional interventions until the exclusive breastfeeding and early complementary feeding (Makanan Pendamping Air Susu Ibu, MP-ASI) phases. Conclusion: The Pagih Book is a comprehensive and innovative integrated nutrition monitoring tool that addresses critical gaps in maternal and child nutrition monitoring during the first 1,000 days of life by systematically combining dietary intake recording, nutritional risk monitoring, and ongoing nutrition education within a single, user-centered framework. Novelty/Originality of this article: This article lies in the development of a book-based nutritional monitoring media that is not only educational, but also integrates quantitative-qualitative intake recording, risk monitoring, and continuity of nutritional interventions from pregnancy to the golden age of children in one integrated instrument.